A green forage diet enhances microbial diversity in buffalo rumen - Angela Salzano; Giovanna Bifulco; Alfio Calanni Macchio; Valentina Longobardi; Francesca Aragona; Giovan Maria Pacelli; Giuseppe Campanile (Revista Científica)
Diet alterations affect the composition of the rumen microbiota and, consequently, the rumen metabolism, animal productivity, and the quality of its products. Aim of the work was to analyze the effects of an experimental feed based on the inclusion of ryegrass green forage (16.1 kg dry matter (DM) and, in kg on DM, 14.4 kg crude protein, 5.0 kg fat, 38.5 kg NDF, 23.4 kg ADF, 33.1 NSC, 15.5 kg and 0.91 Milk forage units; Green group) on the microbial composition of the rumen of buffaloes compared to a traditional total mixed ratio (TMR) diet (16.0 kg DM and, in kg on DM, 14.5 kg crude protein, 4.8 kg fat, 38.0 kg NDF, 24.0 kg ADF, 34.0 NSC, 21.0 kg and 0.93 Milk forage units; Dry group). The forage was just ryegrass at the re-blossoming stage, cut twice a day to avoid any fermentation, and immediately put in the mixing wagon, with no storage, and administered to animals. The forage to concentrates ratio of control buffaloes was 56:44, and that of treated buffaloes was 69:31. The two diets were isonitrogenous and isoenergetic and differed only in the inclusion of green feed in treated buffaloes. The study was carried out over 60 days in a commercial buf-falo dairy farm in southern Italy using lactating Italian Mediterranean dairy buffaloes (n 8/group). Rumen fluid samples were immediately collected at the slaughterhouse, and bacterial genomic DNA was extracted to perform metagenomic analyses. Firmicutes and Bacteroidota were the most abundant phyla in both Dry and Green groups (over 92% of the total bacteria). Al though the abundant microbial taxa of the rumen are not affected by the experimental diet, we observed a significant increase in rare species and an overall increase in total biodiversity in the Green group. Indeed, at the order level, the Peptostreptococcales-Tissierellales, Veillonellales-Selenomonadales, and Bradymonadales groups showed statistically significant differences (p<0.05), with the former bacteria being more abundant in the Dry group and the other two in the Green group. Moreover, at the genus level, Prevotellaceae_YAB2003_group and Colidextribacter were more abundant (p<0.05) in the Dry group, while Selenomonas, Prevotellaceae-UCG-007, Quinella, Oscillospira, and Tyzzerella, were more abundant (p<0.05) in the Green group. We conclude that including green forage in the diet can stimulate a more taxonomically and functionally diverse rumen microbiome with positive effects on microbiota total biodiversity, which might improve the health and productivity of the buffaloes.